From prophecy to projection: the New York Metropolitan Region Study and the rescaling of the urban future, 1956–1968. (2nd January 2021) - Ekman, Peter
ABSTRACT: Between 1956 and 1959, amid far-flung residential and industrial suburbanization and with the joint backing of the Rockefeller Foundation, the Ford Foundation, and the Twentieth Century Fund, an interdisciplinary coterie of scholars from Harvard partnered with New York's Regional Plan Association to produce a widely read ten-volume 'projection' of what the physical plant, political economy, and everyday lives of that metropolis would look like in 1985. This paper considers the New York Metropolitan Region Study as a peculiar, consequential exercise in how postwar urbanists recast urban temporality. Rejecting both the certainties of prophecy and the hazards of mere prediction, the Study sought to establish a new tense for urbanism and a newly disciplined set of methods for making inferences about the urban future on the basis of the past and present. The constituent volumes of the NYMRS garnered various degrees of influence in isolation. The sum total both furthered acceptance of a regional scale of operations for planning and decisively chastened hopes for political intervention on urban and regional futures.